Genetic and Epigenetic Characterization of Pulpal and Periapical Inflammation - Fouad, Ashraf F.; Khan, Asma A.; Silva, Renato M.; Kang, Mo K. (Frontiers in Physiology, 2020)
Pulpal and periapical diseases effect a large segment of the population. The role of microbial infections and host effector molecules in these diseases is well established. However, the interaction between host genes and environmental factors in disease susceptibility and progression is less well understood. Studies of genetic polymorphisms in disease relevant genes have suggested that individual predisposition may contribute to susceptibility to pulpal and periapical diseases. Other studies have explored the contribution of epigenetic mechanisms to these diseases. Ongoing research expands the spectrum of non-coding RNAs in pulpal disease to include viral microRNAs as well. This review summarizes recent advances in the genetic and epigenetic characterization of pulpal and periapical disease. Improved understanding of these mechanisms may aid in disease prevention as well as in improved treatment outcomes.